2021
DOI: 10.1109/access.2021.3084749
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of Commodity DRAMs in Harsh Environments Through Thermoelectric Cooling

Abstract: Today, more and more commodity hardware devices are used in safety-critical applications, such as advanced driver assistance systems in automotive. These applications demand very high reliability of electronic components even in adverse environmental conditions, such as high temperatures. Ensuring the reliability of microelectronic components is a major challenge at these high temperatures. The computing systems of these applications rely on DRAMs as working memory, which are built upon bit cells that store ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For example, a coarse-grained approach such as page retirement [49,60,83,84,88,103] efficiently mitigates a small number 9 These mechanisms commonly fall under the umbrella of memory reliability, availability and serviceability (RAS) features [312][313][314]. 10 Consumers with exceptional reliability needs, such as those targeting extreme or hostile environments (e.g., military, automotive, industrial, extraterrestrial), may take more extreme measures (e.g., custom components [158, 159,[334][335][336][337][338][339][340], redundant resources [93,341,342]) to ensure that memory errors do not compromise their systems. 11 Academic works speculate that commodity DRAM targets a bit error rate (BER) within the range of 10 −16 − 10 −12 [86,92,321,343], but we are not aware of industry-provided values.…”
Section: Application To Today's Commodity Dram Chipsmentioning
confidence: 99%
“…For example, a coarse-grained approach such as page retirement [49,60,83,84,88,103] efficiently mitigates a small number 9 These mechanisms commonly fall under the umbrella of memory reliability, availability and serviceability (RAS) features [312][313][314]. 10 Consumers with exceptional reliability needs, such as those targeting extreme or hostile environments (e.g., military, automotive, industrial, extraterrestrial), may take more extreme measures (e.g., custom components [158, 159,[334][335][336][337][338][339][340], redundant resources [93,341,342]) to ensure that memory errors do not compromise their systems. 11 Academic works speculate that commodity DRAM targets a bit error rate (BER) within the range of 10 −16 − 10 −12 [86,92,321,343], but we are not aware of industry-provided values.…”
Section: Application To Today's Commodity Dram Chipsmentioning
confidence: 99%
“…In realistic applications of systems supporting advanced computations, the temperature can rise even above 100 °C due to extensive data processing and working environments. 33) Therefore, the reliability of both architecture's high-temperature applications (up to 125 °C) needs to be ascertained. At higher temperatures, higher recombination and generation rates degrade states 1 and 0, respectively, which results in a significant degradation in hole concentration over time.…”
Section: Assessment Of 1t-dram Metricsmentioning
confidence: 99%
“…The read‐out current in Figure 20h indicates the three negative current spikes these three times as the gate leakage current and SEE‐induced electrons are generated in the gate insulator through gate voltage. [ 238 ] Variation of the drain current with LET is checked since the current for a “0” is greater than the current for a “1”. A soft error is induced in the device, which further illustrates that HEPs can generate a large number of e–h pairs and change the information in cells.…”
Section: Radiation Effect On Memory Devicesmentioning
confidence: 99%
“…The associate sensitivity increases with the increasing gate length. [239] Yan et al recently reported the SEEs in 1T-DRAM based on indium gallium arsenide on insulator (InGaAs-OI) transistor with high energy proton (HEP) [238] (Figure 20d-i). The HEP ranging from 10 to 100 MeV.cm 2 mg −1 strikes perpendicularly to the channel in different positions, as shown in Figure 20d.…”
Section: Drammentioning
confidence: 99%
See 1 more Smart Citation